Sea anemones in the marine aquarium trade: Market preferences indicate opportunities for mariculture and conservation. Issue 12 (21st October 2021) - Fraser, Nicola; Mangubhai, Sangeeta; Hall, Karina; Scott, Anna
Abstract: Marine aquarium organisms represent some of the highest value products that can be harvested from coral reefs. Collection is extremely selective, and sea anemones are often targeted, leading to reduced densities and localized extinctions in some locations. Currently, there is a lack of information about species' popularity and survival in captivity, and consumer attitudes towards sustainability. This study surveyed aquarists and businesses ( n = 445) from 39 countries between February and October 2018 to help fill these knowledge gaps. Respondent groups indicated similar preferences. The three most desired species were Entacmaea quadricolor, Stichodactyla tapetum and Heteractis magnifica . Size preferences for anemones were typically smaller (tentacle crown diameter of 100–200 mm) than their maximum sizes. Survival time in captivity was generally 12 months or longer, and 20% lived more than 10 years. Respondents indicated that they would prefer to buy captive‐bred rather than wild‐harvested anemones (aquarists 95%, businesses 94%) and would pay more for the former (aquarists 79%, businesses 70%). While potential propagation methods have been established for E. quadricolor, other popular anemones within the marine aquarium trade may also be good candidates for captive breeding. Mariculture could provide alternative livelihoods, reduce collection pressure on wild populations and facilitate the recovery and conservation of depleted anemone populations, particularly in developing island nations from where the majority of anemones are currently sourced.